Effects of non-starch polysaccharide enzymes (Roxazyme G2G and/or Ronozyme VP) on growth performance of nursery pigs fed normal or drought-stressed corn - Jones, Cassandra K.; Franz, E. L.; Frobose, Hyatt L.; DeRouchey, Joel M.; Goodband, Robert D.; Tokach, Michael D.; Bergstrom, J. R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
A total of 360 barrows (PIC 1050 × 337, initially 12.9 lb BW) were used to determine the effects of non-starch polysaccharide enzymes (Roxazyme G2G and/or Ronozyme VP; DSM Nutritional Products, Inc., Parsippany, NJ) on growth performance and nutrient digestibility of nursery pigs fed normal or drought-stressed corn. Initially, corn samples were collected from 34 separate lots and analyzed to find representatives of normal and drought-stressed corn. These same lots were also used in a separate experiment measuring the impact of drought stress on diet manufacturing characteristics. The lot selected to represent the normal corn had a test weight of 55.9 lb/bu, <5 ppb aflatoxin, 15.0% moisture, and contained 0.77% β-glucan. The lot selected to represent drought-stressed corn had a test weight of 54.3 lb/bu, 6 ppb aflatoxin, 14.3% moisture, and 0.83% β-glucan. Pigs were allotted to pens at weaning (d 0) and were acclimated to a common diet for 10 d prior to the start of this experiment. On d 10 post-placement, pigs were weighed and pens of pigs randomly allotted to 1 of 8 dietary treatments in a completely randomized design. Treatments were arranged in a 2 × 4 factorial with main effects of corn (normal vs. drought-stressed) and enzyme inclusion (none vs. 100 ppm Roxazyme G2G vs. 250 ppm Ronozyme VP vs. 100 ppm Roxazyme G2G + 250 ppm Ronozyme VP). Pigs were fed experimental treatments from d 10 to 35 postweaning in two phases. Feed and fecal samples were collected on d 30 postweaning and analyzed to determine apparent total tract digestibility of nutrients. The nutrient concentrations of normal and drought-stressed corn were similar, which resulted in few treatment or main effects differences of corn type or enzyme inclusion. No interactions were observed (P > 0.24) between corn source and enzyme inclusion. Overall (d 10 to 35), there was no effect on ADG or ADFI, but enzyme inclusion tended to improve (P = 0.09) F/G, which was primarily driven by the improved (P = 0.04) feed efficiency of pigs fed Roxazyme G2G in Phase 1 (d 10 to 25 postweaning). In conclusion, drought stress did not alter the non-starch polysaccharide concentration of corn. Because non-starch polysaccharide substrates were similar across treatments, it was not surprising that enzyme inclusion showed little benefit to nursery pig growth performance; however, improved feed efficiency of pigs fed diets containing Roxazyme G2G from d 10 to 25 postweaning warrants further investigation.
Keywords: Non-starch polysaccharide enzymes; Nutrient digestibility; Nursery pig; Corn; Drought-stressed corn